Front Cover. Issue 1 (10th January 2019) - Unknown
Abstract : Myoanatomy of a trochophore larva of the polyplacophoran mollusk Leptochiton asellus . Confocal microscopy projection image depicting muscular elements in graded shades from bright yellow to dark red and cell nuclei in blue. Image provided by Maik Scherholz, Dept. of integrative Zoology, University of Vienna.